Remarks on the Messinian evaporites of Zakynthos Island (Io- nian Sea, Eastern Mediterranean). - Karakitsios, V.; Roveri, M.; Lugli, S.; Manzi, V.; Gennari, R.; Antonarakou, A.; Triantaphyllou, M.; Agiadi, K.; Kontakiotis, G. (Bulletin of the Geological Society of Greece, 2013)
Detailed mapping of the Neogene deposits on Zakynthos Island shows that the Messinian primary evaporite basins, formed over Ionian basement, are delimited by the westernmost outcrop of the Triassic evaporitic diapirs, located west of the Kalamaki-Argasi Messinian gypsum unit. The post-Miocene external Ionian thrust is emplaced west of the Triassic diapirs. Planktonic foraminifera biostratigraphy indicates that primary evaporite accumulation took place probably during the first stage of the Messinian salinity crisis (5.96-5.60 Ma), in shallower parts of a foreland basin, formed over the Pre-Apulian and the Ionian zone basement. Establishment of these depositional environments, before the Ionian thrust emplacement, was probably due to the particularities of the foreland basin, which extended from the external Ionian to the internal Pre-Apulian zone. Field observations, borehole data and an onshore seismic profile show that the Neogene sediments over the Pre-Apulian basement correspond to the foredeep through forebulge domain of the foreland basin, as it is documented from their spatial thickness distribution. In contrast, the Neogene sediments over the Ionian basement correspond to the wedge top of the foreland basin, which was less subsiding, as it is deduced by their reduced thickness. This lower subsidence rate was the result of the concurrent diapiric movements of the Ionian Triassic evaporites. In Agios Sostis area, located over Pre-Apulian basement, the Neogene sequence is intercalated by decametre-thick resedimented blocks consisting of shallow water selenite. To the southeast, this mass-wasting Messinian gypsum passes to mainly gypsum turbidite. In Kalamaki-Argasi area, located over Ionian basement, the shallow water environment led to the deposition of the observed primary gypsum. Erosion of the primary gypsum of both forebulge and wedge top supplied the foreland basin’s depocenter with gypsum turbidites.